Corporate identity management and employees' responses. (2nd January 2017) - Bravo, Rafael; Matute, Jorge; Pina, Jose M.
Abstract: Main goals in this study are to analyse the effects of corporate identity management (CIM) on the employees' responses, and the moderating effects of two employee personality traits: proactive personality and resistance to change. Two hundred and ninety-three branch managers in the banking sector in Spain participated in the study, and their responses were analysed through structural equation modelling. Results show that organizational identification is a key variable to explain the CIM effects on employees' responses. Moreover, employees' proactive personality and resistance to change exert a moderating influence on the way identification leads to extra-role behaviours. Human resource practices should take into account that proactive employees are more prone to externalize their identification by spreading positive WOM. Besides, identification with the organization will lead to loyalty, especially in employees with low resistance to change.